Efektifitas Penggunaan APD Coverall Dan Surgical Gown Pada Petugas Terhadap Paparan COVID-19 : The Effectiveness of Using Personal Protective Equipment Coverall and Surgical Gown on Officers against COVID-19 Exposure - Komalasari, Ratih Indriani (Dohara POAJ, 2022)
Introduction: The Global Corona Virus Disease (COVID-19) pandemic has changed the lives of people all over the world. The very high transmission rate causes this disease to have a much greater impact than diseases caused by previous coronaviruses, such as SARS and MERS. Transmission of SARS-CoV-2 can occur through direct contact, indirect contact, or close contact with an infected person through secretions such as saliva and respiratory tract secretions or respiratory droplets and aerosol-generating actions. The increase in the number of patients causes the burden on hospitals to provide Personal Protective Equipment to increase and the risk of transmission to officers’ increases. The purpose of this study was to determine the effectiveness of the use of Personal Protective Equipment cover all and gowns on officers against exposure to COVID-19. Methods: The method used is a quasi-experimental design with a Nonequivalent Control Group The samples of this study were 34 nurses and were divided into 2 groups. Results: Based on the results of the study, the average of each group, namely in the PPE Cover All user group, the rank was 17.50, the same as the average group of PPE Surgical Gown users, with table U of 144.5, Z value of 0.000 and sig p-value of 1,000 > 0,05. Discussion: This mean that are no differences in average antigen swab results for nurses who use Coverall or Surgical Gown, in other words surgical gowns and coveralls have the same effectiveness in protecting officers from COVID-19.